Pengaruh Penggunaan Media Audio Visual Terhadap Motivasi dan Hasil Belajar PKn di MI: Penelitian Kuantitatif pada Kelas V - Munazirah, Siti (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2022)
Learning motivation and learning outcomes of Civic Education (PKn) in Madrasah Ibtidaiyah (MI) class V still show less than optimal levels, especially due to the limited learning media that are less interesting and interactive. This study aims to analyze the effect of using audio-visual media on the motivation and learning outcomes of Civic Education students in class V MI. The research method used is quantitative with a quasi-experimental design involving two groups of students, namely the experimental group using audio-visual media and the control group using conventional methods. Data were collected through learning motivation instruments and learning outcome tests, then analyzed using statistical tests to test the significance of differences between groups. The results showed that the use of audio-visual media significantly increased students' learning motivation and Civic Education learning outcomes compared to conventional learning methods. These findings strengthen the theory of multimedia learning and the ARCS motivation model, while providing practical implications for the development of more effective and interesting Civic Education learning in MI. The recommendation of this study is the systematic integration of audio-visual media in Civic Education learning to improve the quality of civic education at the elementary level.